Comprehensive analysis of splicing variants in corneal endothelial cells of patients with Fuchs endothelial corneal dystrophy - Taichi Yuasa; Yuichi Tokuda; Masakazu Nakano; Kei Tashiro; Theofilos Tourtas; Ursula Schlötzer-Schrehardt; Friedrich Kruse; Noriko Koizumi; Naoki Okumura (Scientific Reports)
Abstract Trinucleotide repeat (TNR) expansion in the transcription factor 4 (TCF4) gene represents the most prevalent genetic risk factor for Fuchs endothelial corneal dystrophy (FECD) and may cause dysfunction of splicing regulators. We investigated differential alternative splicing (DAS) events in corneal endothelial cells (CECs) from FECD patients with and without TCF4 TNR expansion through RNA-Seq analysis. We identified distinct splicing profiles among control subjects, FECD patients with TNR expansion, and FECD patients without TNR expansion. Skipped Exon events constituted approximately 50% of all DAS events across all comparisons, with the remaining events distributed among alternative 3’ splice site, alternative 5’ splice site, mutually exclusive exon, and retained intron categories. Motif analysis in FECD patients with TNR expansion revealed several RNA-binding proteins, including MBNL1, as potential regulators of these splicing alterations. Computational analysis demonstrated that 34% of Skipped Exon events in the TNR expansion group significantly impacted protein structure. This comprehensive analysis revealed distinct alternative splicing signatures in FECD, particularly in cases with TNR expansion, suggesting a crucial role for aberrant splicing in FECD pathogenesis.